Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1071/en18073
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic concentrations and speciation in Australian and imported rice and commercial rice products

Abstract: Environmental contextIn countries where inhabitants are not exposed to arsenic-contaminated drinking water, food is the major source of potentially toxic inorganic arsenic. To complement the existing worldwide dataset on arsenic in rice, data are presented on Australian- and overseas-grown rice, and assessed in terms of possible risk. Only a diet comprising multiple serves of some rice products per day poses a potential risk to young children. AbstractArsenic concentrations and speciation measurements were det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 82 publications
(127 reference statements)
2
6
0
Order By: Relevance
“…Among the 140 rice samples, total As concentrations varied from 25.1 to 370 μg/kg (mean 143 μg/kg, median 132 μg/kg); iAs ranged from 18.3 to 220 μg/kg (mean 97.6 μg/kg, median 90.0 μg/kg); DMA ranged from 4.39 to 94.1 μg/kg (mean 29.4 μg/kg, median 28.0 μg/kg); and DMMTA ranged from <0.20 (i.e., limit of detection, being for 2 out of 140 samples) to 30.4 μg/kg (mean 10.4 μg/kg, median 10.0 μg/kg) (Figure A and Table S2). The ranges and means of total As and iAs obtained in the present study are similar to those reported previously for global studies of As in rice. ,,,, Among the 140 rice samples, 12 samples (5%) exceeded the EU and Chinese limits for iAs in rice of 200 μg/kg. The proportion of As present as iAs varied from 41 to 98% (mean 68%), as DMA from 1.3 to 48% (mean 24%), and as DMMTA from 1.4 to 16% (mean 8%) (Figure B).…”
Section: Resultssupporting
confidence: 88%
“…Among the 140 rice samples, total As concentrations varied from 25.1 to 370 μg/kg (mean 143 μg/kg, median 132 μg/kg); iAs ranged from 18.3 to 220 μg/kg (mean 97.6 μg/kg, median 90.0 μg/kg); DMA ranged from 4.39 to 94.1 μg/kg (mean 29.4 μg/kg, median 28.0 μg/kg); and DMMTA ranged from <0.20 (i.e., limit of detection, being for 2 out of 140 samples) to 30.4 μg/kg (mean 10.4 μg/kg, median 10.0 μg/kg) (Figure A and Table S2). The ranges and means of total As and iAs obtained in the present study are similar to those reported previously for global studies of As in rice. ,,,, Among the 140 rice samples, 12 samples (5%) exceeded the EU and Chinese limits for iAs in rice of 200 μg/kg. The proportion of As present as iAs varied from 41 to 98% (mean 68%), as DMA from 1.3 to 48% (mean 24%), and as DMMTA from 1.4 to 16% (mean 8%) (Figure B).…”
Section: Resultssupporting
confidence: 88%
“…This is consistent with previous Australian results for rice-based foods [23]. The high tAs mean concentration in Australia probably resulted from the higher As concentrations in Australian rice than imported rice [13,24,40] and the higher Australian maximum level for tAs in rice compared to many countries (Table 1).…”
Section: The Relationship Between Tas Concentration and Country Of Orsupporting
confidence: 92%
“…soils and rocks (Palmer et al 2021) and the historical use of herbicides such as cacodylic acid (Limmer and Seyfferth 2020). There is a concern about human exposure to As, particularly for infants, through the consumption of rice and processed rice products (Sohn 2014;Maher et al 2018).…”
Section: Introductionmentioning
confidence: 99%